Microalgae: The Future Supply House of Biohydrogen and Biogas - Wang, Kexin; Khoo, Kuan Shiong; Chew, Kit Wayne; Selvarajoo, Anurita; Chen, Wei-Hsin; Chang, Jo-Shu; Show, Pau Loke (Frontiers in Energy Research, 2021)
The non-renewable nature of fossil energy and the environmental pollution caused by its use, such as haze, make it very urgent to develop clean and efficient renewable energy. By using microalgae biomass as an alternative raw material energy sources like biohydrogen, methane can be produced through fermentation and photosynthesis. Unlike solar energy, which has the disadvantages of low energy density, instability and difficulty in storage, biohydrogen and biogas are one of the novel ideal energy sources at present. The utilization of microalgae has various attractive prospects in their production due to its cost-effectiveness, renewable biomass and ease of scaling-up technology. This paper discusses the latest microalgae biomass biohydrogen and biogas production technology including integrated biorefinery systems, co-production or mixed production techniques and puts forward the key problems to be solved in the development of microalgae biohydrogen production technology.